Very Facile Polarity Umpolung and Noncovalent Functionalization of Inorganic Nanoparticles: A Tool Kit for Supramolecular Materials Chemistry - Zeininger, Lukas; Petzi, Stefanie; Schönamsgruber, Jörg; Portilla Berlanga, Luis; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2015)
The facile assembly of shell-by-shell (SbS)-coated nanoparticles [TiO2 -PAC16 ]@shell 1-7 (PAC16 = hexadecylphosphonic acid), which are soluble in water and can be isolated as stable solids, is reported. In these functional architectures, an umpolung of dispersibility (organic apolar versus water) was accomplished by the noncovalent binding of ligands 1-7 to titania nanoparticles [TiO2 -PAC16 ] containing a first covalent coating with PAC16. Ligands 1-7 are amphiphilic and form the outer second shell of [TiO2 -PAC16 ]@shell 1-7. The tailor-designed dendritic building blocks 3-5 contain negative and positive charges in the same molecule, and ligands 6 and 7 contain a perylenetetracarboxylic acid dimide (PDI) core (6/7) as a photoactive reporter component. In the redox and photoactive system [TiO2 -PAC16 ]@shell 7, electronic communication between the inorganic core to the PDI ligands was observed.